Life stories as a formative exercise for old women - Ladogana, Manuela (Studi sulla Formazione/Open Journal of Education, 2019)
Starting from the idea that autobiography can be a way of caring-for-oneself – understood as an opportunity to rethink and re-engineer oneself at any age, this contribution will underscore the pedagogical potential of autobiographical narration as an existentially deliberate formative exercise capable of restoring a desire for ulteriority even at an age nearing the end of life. Specifically, an experiment carried out among elderly women was carried out as part of the “places and forms of care” workshop.